LncRNA NEAT1 aggravates human microvascular endothelial cell injury by inhibiting the Apelin/Nrf2/HO-1 signalling pathway in type 2 diabetes mellitus with obstructive sleep apnoea - Kai Chen; Baiqing Ou; Quan Huang; Daqing Deng; Yi Xiang; Fang Hu (Epigenetics)
Long noncoding RNAs (lncRNAs) regulate the progression of type 2 diabetes mellitus complicated with obstructive sleep apnoea (T2DM-OSA). However, the role of the lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) in T2DM-OSA remains unknown. This study aimed to reveal the function of NEAT1 in T2DM-OSA and the underlying mechanism. KKAy mice were exposed to intermittent hypoxia (IH) or intermittent normoxia to generate a T2DM-OSA mouse model. HMEC-1 cells were treated with high glucose (HG) and IH to construct a T2DM-OSA cell model. RNA expression was detected by qRT-PCR. The protein expression of Apelin, NF-E2-related factor 2 (Nrf2), haem oxygenase-1 (HO-1), and up-frameshift suppressor 1 (UPF1) was assessed using western blot. Cell injury was evaluated using flow cytometry, enzyme-linked immunosorbent assay, and oxidative stress kit assays. RIP, RNA pull-down, and actinomycin D assays were performed to determine the associations between NEAT1, UPF1, and Apelin. NEAT1 expression was upregulated in the aortic vascular tissues of mice with T2DM exposed to IH and HMEC-1 cells stimulated with HG and IH, whereas Apelin expression was downregulated. The absence of NEAT1 protected HMEC-1 cells from HG- and IH-induced damage. Furthermore, NEAT1 destabilized Apelin mRNA by recruiting UPF1. Apelin overexpression decreased HG- and IH-induced injury to HMEC-1 cells by activating the Nrf2/HO-1 pathway. Moreover, NEAT1 knockdown reduced HG- and IH-induced injury to HMEC-1 cells through Apelin. NEAT1 silencing reduced HMEC-1 cell injury through the Apelin/Nrf2/HO-1 signalling pathway in T2DM-OSA.Abbreviations: LncRNAs, long non-coding RNAs; T2DM, type 2 diabetes mellitus; OSA, obstructive sleep apnoea; NEAT1, nuclear paraspeckle assembly transcript 1; IH, intermittent hypoxia; HMEC-1, human microvascular endothelial cells; HG, high glucose; Nrf2, NF-E2-related factor 2; UPF1, up-frameshift suppressor 1; HO-1, haem oxygenase-1; qRT-PCR, quantitative real-time polymerase chain reaction; ELISA, enzyme-linked immunosorbent assay; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; TNF-α, tumour necrosis factor-α; CCK-8, Cell Counting Kit-8; IL-1β, interleukin-1β; ROS, reactive oxygen species; MDA, malondialdehyde; SOD, superoxide dismutase; RIP, RNA immunoprecipitation; SD, standard deviations; GSH, glutathione; AIS, acute ischaemic stroke; HMGB1, high mobility group box-1 protein; TLR4, toll-like receptor 4.